Ticagrelor Use in Indian Patients Undergoing Neuroendovascular Procedures: A Single Center Experience - Karan, Vivek (Neurointervention, 2019)
PURPOSE: A safe and efficacious antiplatelet drug is needed for patients with clopidogrel resistance who undergo neuroendovascular procedures. Ticagrelor is a new reversibly binding, oral, direct-acting P2Y receptor antagonist with no known resistance. We describe our clinical experience using ticagrelor for neuroendovascular procedures in Indian patients with clopidogrel resistance at the NH Institute of Neurosciences, Narayana Health City, Bangalore. MATERIALS AND METHODS: We retrospectively reviewed our endovascular procedure database for all patients with predefined clopidogrel resistance. Clopidogrel resistance was defined as P2Y12 inhibition <40%. Patients were administered ticagrelor along with aspirin prior to the procedure. RESULTS: Of 127 patients, 32 (25%) were non-responders to clopidogrel (22 [69%] males, 10 [31%] females; median age, 54 years [range, 20–75]). All patients were treated with a 180-mg loading dose of ticagrelor, followed by 90 mg twice daily. Twenty patients (63%) underwent endovascular intervention for intracranial aneurysm, two (6%) for dissecting aneurysms, nine (28%) for stenotic lesions, and one (3%) for carotico-cavernous fistula. No patient experienced any adverse effects related to the use of Ticagrelor in the postoperative period. CONCLUSION: Ticagrelor is an effective alternative to clopidogrel for use in conjunction with aspirin in patients with clopidogrel resistance. None of our patients had adverse effects from ticagrelor. Drug cost, twice-daily dosing, and risk of faster platelet aggregation activation after discontinuation should be taken into consideration prior to its use in such patients.